Pengaruh Inflasi dan Nilai Tukar terhadap Nilai Aktiva Bersih Reksa Dana Saham dengan Pendekatan Error Correction Model - Pamungkas, Wisnu Bayu; Situngkir, Tiar Lina (Peneliti.net, 2024)
Mutual funds are a good place to invest for novice investors to get profits in the future. Therefore, mutual funds really need to be studied by including macroeconomic variables, namely inflation and exchange rates. The purpose of this study is to analyze the effect of inflation and exchange rates on Net Asset Value (NAV) of equity funds. The method used in this study is the Error Correction Model. The results show that in the long run the inflation variable has a significant positive effect on the NAV of equity funds. However, the exchange rate variable has a significant negative effect. Furthermore, in the short-term estimation, inflation has no effect on the NAV of equity funds. Then the exchange rate has a significant negative effect. Simultaneously (together) in the long run has a significant influence on the NAV of equity funds. This is inversely proportional to the short-term estimation results which state that simultaneous inflation and exchange rates have no effect on the NAV of equity funds. The data used in this study is the period 2018 – 2022.